Xenotransplantation - current social, ethical, religious, and legal aspects - Kucharczyk, Emilia; Busłowicz, Tomasz; Puła, Michał; Kucharczyk, Natalia; Zakrocka, Martyna (Journal of Education, Health and Sport, 2023)
Introduction: Xenotransplantology, the field of transplantation involving organs or tissues between different species, holds great promise for addressing the global organ shortage crisis. However, the development of new technologies without proper legislative preparation raises significant moral and ethical considerations. This paper provides an overview of the current state of xenotransplantology, highlighting its revolutionary potential alongside the moral dilemmas it entails. Aim of the study: The aim of this study is to assess current social, ethical, religious, and legal trends regarding the issue of xenotransplantation. Materials and methods: To obtain up-to-date information concerning trends in xenotransplantation, a review of the PubMed and Google Scholar databases, along with the latest legislative reports in both Europe and Poland, was performed. Conclusions: Firstly, the authors briefly report on the current situation concerning transplantology and the widely spread organ donor crisis. Next, the issue of species boundaries and the moral status of non-human animals is addressed. The assessment of ethical implications of utilizing animals as organ donors is examined, along with the legal acts regulating this issue. Moreover, the authors attempt to evaluate the cultural and religious differences related to this concern. Furthermore, this study discusses the allocation and distribution of xenotransplants, considering issues of justice, fairness, and access to this innovative medical technology. Lastly, the paper delves into the risks and uncertainties associated with xenotransplantation, including the possibility of cross-species disease transmission and intensified course of organ rejection disease.